Accretion versus erosion and sediment transfer balance near the subduction interface - Lallemand, Serge; Peyret, Michel; Arcay, Diane; Heuret, Arnauld (Comptes Rendus. Géoscience, 2024)
The nature and amount of sediment transferred from one plate to the other near the subduction interface partly determines the tectonic and seismogenic regime of a margin. Examination of over 500 multichannel seismic lines has enabled us to build up a global database of subduction zone front characteristics at unprecedented spatial resolution. The total thickness of sediment in the trench below the deformation front, as well as that of the subduction channel at a distance from the trench, combined with other indices such as the tectonic regime of the forearc or the migration of the volcanic front, have enabled us to revisit the accretionary or erosional character of active margins. Preliminary conclusions, based on ${\sim }$3/4 of sufficiently documented subduction zones, show a predominance of the erosive character of subduction over the last million years. The flux of solid matter through the shallow part of the subduction channel is of the order of 1.5 km$^{3}$/yr, and that of pore fluids 0.4 km$^{3}$/yr. Some subduction zones, such as the Mediterranean, are characterized by exceptional solid flux in the channel, while fluid flux is comparatively moderate. This is due to the fact that channel sediments are compacted even before subduction. Overall, fluid flux in the channel is greater under erosive margins, due to the higher rate of subduction and often higher porosity. Maximum porosity in the channel is reached when there is neither accretion nor tectonic erosion.